2022
DOI: 10.1111/cea.14261
|View full text |Cite
|
Sign up to set email alerts
|

From trained immunity in allergy to trained immunity‐based allergen vaccines

Abstract: Innate immune cells experience long lasting metabolic and epigenetic changes after an encounter with specific stimuli. This facilitates enhanced immune responses upon secondary exposition to both the same and unrelated pathogens, a process termed trained immunity. Trained immunity-based vaccines (TIbV) are vaccines able to induce innate immune memory, thus conferring heterologous protection against a broad range of pathogens. While trained immunity has been well documented in the context of infections and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Different ventures of existing vaccines or viral components to induce trained immunity seek to improve conventional vaccines toward the new formulations of the so-called trained immunity-based vaccines (TIbV), aimed at stimulating broader responses beyond their specific antigens, an approach that could make it possible to afford proper resistance against viral outbreaks [ 104 , 105 , 106 , 107 ]. However, this might not be the case for allergen vaccines.…”
Section: Trained Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different ventures of existing vaccines or viral components to induce trained immunity seek to improve conventional vaccines toward the new formulations of the so-called trained immunity-based vaccines (TIbV), aimed at stimulating broader responses beyond their specific antigens, an approach that could make it possible to afford proper resistance against viral outbreaks [ 104 , 105 , 106 , 107 ]. However, this might not be the case for allergen vaccines.…”
Section: Trained Immunitymentioning
confidence: 99%
“…However, this might not be the case for allergen vaccines. In a recent study Benito-Villalvilla et al, it was demonstrated that allergoid–mannan conjugates, which serve as next-generation vaccines for allergen-specific immunotherapy (AIT), contribute to allergen tolerance by the differentiation of monocytes into tolerogenic dendritic cells (DCs), but lack the capacity to induce any trained immunity effects [ 107 , 108 ]. Similarly, the innate counterparts of T cells—innate lymphoid cells (ILCs)—primed by IL-33 or allergic inflammation mount enduring memory-like responses against other allergens, which can serve as double-edged sword, on the one side affording proper protection against infectious diseases and, on the other side, by contributing to pathology or disease progression [ 109 , 110 , 111 ].…”
Section: Trained Immunitymentioning
confidence: 99%
“…For example, the presence of stimuli such as dexamethasone (Dex), vitamin D3 (VitD3), rapamycin, or allergoid-mannan conjugates promotes the differentiation of monocytes into tolerogenic DCs or immunosuppressive macrophages ( 22 26 ). Conversely, monocytes exposed with whole heat-inactivated Candida albicans or β-glucans from its cell wall give raise to trained monocyte-derived macrophages ( 27 29 ). Here, we show that LPS-stimulated WIN-hmoDCs displayed reduced production of the pro-inflammatory cytokines TNFα, IL-1β and IL-6 without changes in IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Postsynaptic reprogramming could be useful during immunization, as innate training confers heterologous protection [68][69][70] from other diseases [71,72] due to the nonspecific trained immunity-based effect of vaccines [73,74]. Indeed, this effect could also increase the efficacy of existing vaccines [75], or bring forth a novel ground-breaking generation of trained immunitybased vaccines to fight infection [76][77][78][79][80] or allergy [81]. The underlying rationale would be that psDC could enhance innate and adaptive responses.…”
Section: Perspectives On the Applications Of Postsynaptic Reprogrammingmentioning
confidence: 99%